The Exocyst Component Sec3 Controls Egg Chamber Development Through Notch During Drosophila Oogenesis - Wan, Ping; Zheng, Sumei; Chen, Lai; Wang, Dou; Liao, Ting; Yan, Xueming; Wang, Xiaoji (Frontiers in Physiology, 2019)
The exocyst complex plays multiple roles via tethering secretory or recycling vesicles to the plasma membrane. Previous studies have demonstrated that the exocyst contains eight components, which possibly have some redundant but distinct functions. It is therefore interesting to investigate the biological function of each component. Here, we found that Sec3, one component of exocyst complex, is involved in Drosophila egg chamber development. Loss of sec3 results in egg chamber fusion through the abolishment of cell differentiation. In addition, loss of sec3 increases cell numbers but decreases cell size. These defects phenocopy Notch pathway inactivation. In line with this, loss of sec3 indeed leads to Notch protein accumulation, suggesting that the loss of Sec3 inhibits the delivery of Notch onto the plasma membrane and accumulates inactive Notch in the cytoplasm. Loss of sec3 also leads to the ectopic expression of two Notch pathway target genes, Cut and FasciclinIII, which should normally be downregulated by Notch. Altogether, our study revealed that Sec3 governs egg chamber development through the regulation of Notch, and provides fresh insights into the regulation of oogenesis.